The importance of industrial education - Geary, H. L. (Statistical and Social Inquiry Society of Ireland, 1876)
In the course of some recent investigations which involved enquiry into the working and results of Reformatory and Industrial Schools, it seemed to me that the subject had not yet received the attention it merited, on the part of many interested in the solution of social problems?living beyond the circle of those immediately engaged in the working of such establishments. And it is in the conviction that the principle requires more extended application, in the interests of the honest labouring classes, that I venture to submit the contents of this paper for the consideration of the Society.
Read before the Society, 27 June 1876
Keywords: Industrial schools; Reformatory education; Irish education system; 314.15